POLYMYOSITIS/DERMATOMIOSITIS: DIFFERENTIAL DIAGNOSIS - O. A. Antelava (Научно-практическая ревматология)
The lecture considers the problem of rare systemic connective tissue diseases, such as idiopathic inflammatory myopathies (IIMs). It underlines the clinical and immunological heterogeneity of their subtypes, which defines therapeutic tactics and prognosis. The diagnostic criteria for IIMs are given. A differential diagnostic algorithm based on the exclusion of phenotypically similar forms of myopathies of different genesis is proposed.